2020
DOI: 10.1007/s11064-020-02956-w
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPAR-β/δ Attenuates Brain Injury by Suppressing Inflammation and Apoptosis in a Collagenase-Induced Intracerebral Hemorrhage Mouse Model

Abstract: Brain injury has been proposed as the major cause of the poor outcomes associated with intracerebral hemorrhage (ICH). Emerging evidence indicates that the nuclear receptor, peroxisome proliferator-activated receptor β/δ (PPAR-β/δ), plays a crucial role in the pathological process of central nervous impairment. The present study was undertaken to evaluate the protective effects of PPAR-β/δ activation using a selective PPAR-β/δ agonist, GW0742, against brain injury after ICH in a mouse model. ICH was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
(76 reference statements)
2
11
0
Order By: Relevance
“…These findings of a role for endogenous PPAR-δ in neuroprotection does correspond with past reports of neuroprotective effects of synthetic PPAR-δ agonists GW0742 and GW501516 in cultured neurons ( 64 , 65 ) and in murine models of Alzheimer's disease ( 66 , 67 ), stroke ( 68 71 ), Parkinson's disease ( 72 , 73 ), and Huntington's disease ( 65 ). In a stroke model, activating PPAR-δ limited infarct size in the CNS by mitigating oxygen-glucose-deprivation-induced death in the vascular endothelial cells ( 71 ).…”
Section: Discussionsupporting
confidence: 90%
“…These findings of a role for endogenous PPAR-δ in neuroprotection does correspond with past reports of neuroprotective effects of synthetic PPAR-δ agonists GW0742 and GW501516 in cultured neurons ( 64 , 65 ) and in murine models of Alzheimer's disease ( 66 , 67 ), stroke ( 68 71 ), Parkinson's disease ( 72 , 73 ), and Huntington's disease ( 65 ). In a stroke model, activating PPAR-δ limited infarct size in the CNS by mitigating oxygen-glucose-deprivation-induced death in the vascular endothelial cells ( 71 ).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, it has been shown that activation of the PPAR pathway prevents inflammatory responses throughout the body and reverses tissue damage (Kurtak, 2014). Besides, PPAR pathway is an important factor in reparative processes of various forms of brain injury (Li et al, 2019;Oyagbemi et al, 2020;Tang et al, 2020). On the other hand, our analysis showed that Parkinson's disease pathway was negatively enriched in the up-regulated lncRNAs.…”
Section: Discussionmentioning
confidence: 67%
“…5 µm). 13 C NMR spectra were obtained using a Varian UNITY 400 spectrometer and 1 H NMR spectra were recorded using a Varian INOVA 500 spectrometer. Optical rotation was detected using a Jasco P-1020 polarimeter.…”
Section: Methodsmentioning
confidence: 99%